Reimagining Efl Presentations: Students’ Experiences And Engagement Through Canva - Yassina Fadillah; Lutfi Istikharoh (UM Purwokerto Press, 2026)
This study aims to explore students' perceptions of using Canva as a digital presentation tool in English as a Foreign Language (EFL) learning, focusing on engagement levels, utilization of multimedia elements, and their experiences compared to other presentation tools. Using a descriptive quantitative approach supplemented with qualitative data, data was collected through closed-ended questionnaires and open-ended responses from a number of students. The results of the study show that students gave very positive responses to Canva, particularly in terms of ease of use, attractive visual appearance, and collaborative features. In general, Canva is considered capable of increasing students' confidence and engagement when giving presentations. Thematic analysis of the qualitative responses also revealed that features such as ready-made templates, animations, graphic elements, and online collaboration are the main attractions. Despite challenges such as dependence on internet connectivity and limited access to premium features, students still rated Canva as superior to other presentation tools. This study concludes that Canva can enrich the learning experience through a student-cantered multimodal approach, while supporting independence and digital literacy in the context of English language learning